L'expression hypocoristique en baoulé - Yao JEAN-MARC YAO (Altralang Journal)
ABSTRACT: To express affective purposes, Baule language uses hypocoristics denominations to name individuals (human or animals) as all the world's languages do. However, the creation method of hypocoristics in baule is different from what is commonly seen elsewhere. Really, in European languages like french or romanian the most productive creation processes of hypocoristics are truncation, reduplication, derivation and conventional hypocoristics words. Baoulé language seems only to admit one hand conventional hypocoristics and in the other hand some contextual hypocoristics use. This paper consists on introducing the conventional hypocoristics setup in baule before focusing on certain hypocoristics use of marquers not specifically created for that purpose. We follow a synchronic trend based on empirical facts. The politeness theory and phonstylistics are call upon to serve as theoritical basis of the analysis